First record of two trichodinid ectoparasites (Ciliophora: Trichodinidae) from Chittagong, Bangladesh - Asmat, GSM; Naher, L; Sultana, N; Habib, MMA (Journal of Biodiversity Conservation and Bioresource Management, 2018)
During parasitological surveys in Chittagong, Bangladesh two species of trichodinid ectoparasites belonging to the genera Tripartiella Lom, 1959 and Trichodina Ehrenberg, 1830 were collected from the gills of Rita rita (Hamilton, 1822) and Channa striata (Bloch, 1793) from January to December 2001. Tripartiella orthodens Basson and Van As, 1987 was recorded from the gills of R. rita in the Karnaphuli River systems, and Trichodina cobitis Lom, 1961 from C. striata in a household pond. Description, photomicrographs and morphometric data of these ciliates are provided along with their prevalence and intensity of infection. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 11-18